1998
DOI: 10.1021/ma971419l
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Morphologies of Self-Assembled Crew-Cut Aggregates of Amphiphilic PS-b-PEO Diblock Copolymers in Solution

Abstract: A wide range of bilayer aggregates, among them tubules, vesicles, large compound vesicles (LCVs), and lamellae, were prepared from various polystyrene-b-poly(ethylene oxide) (PS-b-PEO) diblock copolymers, and studied by transmission electron microscopy (TEM). The preparation method involved copolymer dissolution in DMF at room temperature, followed by the addition of water. In addition, it was found that aggregates of various morphologies can be prepared from an identical block copolymer by changing the solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
358
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(377 citation statements)
references
References 69 publications
16
358
2
1
Order By: Relevance
“…As the curing of the resin progresses, the unstable, distorted spherical micelles adhesively collide with neighboring micelles and form a structure similar to a string of interconnected spheres reported by Discher and others. 39,45,46 From this collection of interconnected spheres, the more stable wormlike micelle structure forms. The high magnification TEM images of the uncured Sample 8, shown in Figure 7, support this method of wormlike micelle formation.…”
Section: Resultsmentioning
confidence: 99%
“…As the curing of the resin progresses, the unstable, distorted spherical micelles adhesively collide with neighboring micelles and form a structure similar to a string of interconnected spheres reported by Discher and others. 39,45,46 From this collection of interconnected spheres, the more stable wormlike micelle structure forms. The high magnification TEM images of the uncured Sample 8, shown in Figure 7, support this method of wormlike micelle formation.…”
Section: Resultsmentioning
confidence: 99%
“…The type of structure formed is due to the inherent curvature of the molecule, which can be estimated through calculation of its dimensionless packing parameter, p. Figure 2. Transmission electron micrographs of: a) 'hamburger' micelles, [12] b) helical micelles, [23] c) bilayer tubules, [29] and d) mixtures of polymer vesicles and 'octopi' structures. [18] (Reproduced with permission from ref.…”
Section: Block Copolymer Vesiclesmentioning
confidence: 99%
“…[18] (Reproduced with permission from ref. [12,18,23,29] membrane permeability, with the addition of protein channels [57] and membrane plasticization [58,59] greatly increasing trans-membrane diffusion. Biological membranes are much more complex and sophisticated than the simple vesicle structures reported here, since the former contain many types of proteins and cellular recognition elements.…”
Section: Block Copolymer Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The core is formed by the hydrophobic segments, whereas the hydrophilic segments form the shell which provides solubility in water and stability to the aggregates. A number of hydrophilic polymers have been used but poly(ethylene glycol) PEO is the most common due to its unique properties, and many studies on PEO-based copolymers have been reported [10][11][12] . Recently, poly(2-hydroxyethyl methacrylate) (PHEMA)) has attracted great interest because this polymer exhibits excellent biocompatibility 13 and good blood compatibility 14 .…”
Section: Introductionmentioning
confidence: 99%